Entre el triunfo de la agonía y la Lucidez de las Lágrimas: La Desesperación profanadora de Emil Cioran (2022)
The thought of E. M. Cioran (1911-1995) has been always guided by the omnipresence of an existential pessimism, in which the notion of the Fall indelibly informs his mental framework. Given that ontological exile is one of the cornerstones of his reflective catalogue, the capital tragedy, for Cioran, would be a Fall in Being and Time, the inescapability of existence that finds a particular resonance in a title such as The Trouble of Being Born (1973). Not denying the validity of these philosophical premises, this article aims, however, at filling what we believe to be a gap within the field of cioranian studies, namely the recognition of the pertinence, for a correct understanding of this author’s work, of the presence of humour and of irony in his forma mentis, drawing upon the concept of profanation highlighted by Giorgio Agamben, the concept of humour explored by Julio Cortázar, and the concept of disaster by Maurice Blanchot.